2019
DOI: 10.1038/s41598-019-56735-x
|View full text |Cite
|
Sign up to set email alerts
|

Straw phytolith for less hazardous open burning of paddy straw

Abstract: Rice production helps feed at least half of the world’s population but generates approximately one billion tonnes of straw residue per annum. On-site open burning of rice straw after harvesting is common in recent times because there has been less demand for rice straw to use as fuel and fodder. Due to health and climate change concerns, open burning, which results in biomass losses, smog and emissions of green house gases, e.g., CO2, has been widely criticized and banned in many countries. Little is known abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 26 publications
0
9
0
1
Order By: Relevance
“…Jerami mengandung 35,61% selulosa, 26,96% hemiselulosa dan 10,79% lignin (Syazwanee, 2018), sehingga dapat dimanfaatkan sebagai bahan baku tisue. Produk tisu yang dihasilkan dari jerami bersifat biodegradable (Nguyen, 2019). Tisu kering berbahan jerami akan ditambah dengan minyak aroma terapi cirus/jeruk yang dapat meredakan kecemasan sehingga membantu menenangkan pikiran petani.…”
Section: Pendahuluanunclassified
“…Jerami mengandung 35,61% selulosa, 26,96% hemiselulosa dan 10,79% lignin (Syazwanee, 2018), sehingga dapat dimanfaatkan sebagai bahan baku tisue. Produk tisu yang dihasilkan dari jerami bersifat biodegradable (Nguyen, 2019). Tisu kering berbahan jerami akan ditambah dengan minyak aroma terapi cirus/jeruk yang dapat meredakan kecemasan sehingga membantu menenangkan pikiran petani.…”
Section: Pendahuluanunclassified
“…The simple incineration of waste S. psammophila not only fails to make rational use of calorific value, but also causes serious environmental pollution such as dust, sulfur oxides, and nitrogen oxides. Therefore, it is particularly important to improve the application of waste sand ash resources and realize the "turning waste into treasure" of waste sand ash resources (Nguyen and Nguyen 2019). Salix psammophila contains 36.9% cellulose, 35.0% hemicellulose, 24.8% lignin, a small amount of ash, tannin, and lipids, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Besides these methods, an alternative approach uses the chemical composition to identify burned phytoliths. Although some research has demonstrated the content of Pb, SiO 2 , and C occluded in phytoliths could change due to heating (Jones and Beavers, 1964;Nguyen and Nguyen, 2019;Wu et al, 2014), only C has been invoked as a fire indicator. The darkened color of burned phytoliths is probably derived from the oxidation of phytolith-occluded carbon (PhytOC), and is used to distinguish burned from unburned phytoliths (Gu et al, 2008;Parr, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Plants with high phytolith carbon sequestration rates play an important role in increasing the global carbon sink and mitigating global CO 2 emissions (Chen et al, 2019;Meng et al, 2013;Song et al, 2017). However, the combustion of plants might influence the chemical composition of phytoliths and their taphonomy in soils (Blecker et al, 2006;Nguyen and Nguyen, 2019;Nguyen et al, 2021).…”
Section: Introductionmentioning
confidence: 99%